Massive hemorrhage from an aortoesophageal fistula caused by esophageal stent implantation: A case report and literature review - Zhan, Yefei (Medicine (Baltimore), 2019)
RATIONALE: Aortoesophageal fistula (AEF) is the direct communication between the aorta and esophagus, which can cause fatal hemorrhage, and its incidence increased with the use of an esophageal stent (ES). PATIENT CONCERNS: A 79-year-old man was admitted due to hemodynamic shock with massive hematemesis caused by AEF 1 month after the implantation of an ES. DIAGNOSES: Computed tomography angiography visualized an AEF with an ulcer-like projection on the aortic arch where the ES was placed. Angiography of the aorta revealed extravasation of contrast media from the aortic arch into the stented esophagus, which confirmed the diagnosis. INTERVENTIONS: Thoracic endovascular aortic repair (TEVAR) was performed for massive hematemesis caused by ES-related, AEF but did not solve the underlying problem, leading to the second fatal hemorrhage. LESSONS: TEVAR for the unique treatment of ES-related AEF is feasible in certain cases but may lead to collapse after a specific period.